Room‐Temperature Magnetic Skyrmions and Large Topological Hall Effect in Chromium Telluride Engineered by Self‐Intercalation - Zhang, Chenhui; Liu, Chen; Zhang, Junwei; Yuan, Youyou; Wen, Yan; Li, Yan; Zheng, Dongxing; Zhang, Qiang; Hou, Zhipeng; Yin, Gen; Liu, Kai; Peng, Yong; et al. (Advanced materials (Weinheim), 2023)
Room‐temperature magnetic skyrmion materials exhibiting robust topological Hall effect (THE) are crucial for novel nano‐spintronic devices. However, such skyrmion‐hosting materials are rare in nature. In this study, a self‐intercalated transition metal dichalcogenide Cr1+xTe2 with a layered crystal structure that hosts room‐temperature skyrmions and exhibits large THE is reported. By tuning the self‐intercalate concentration, a monotonic control of Curie temperature from 169 to 333 K and a magnetic anisotropy transition from out‐of‐plane to the in‐plane configuration are achieved. Based on the intercalation engineering, room‐temperature skyrmions are successfully created in Cr1.53Te2 with a Curie temperature of 295 K and a relatively weak perpendicular magnetic anisotropy. Remarkably, a skyrmion‐induced topological Hall resistivity as large as ≈106 nΩ cm is observed at 290 K. Moreover, a sign reversal of THE is also found at low temperatures, which can be ascribed to other topological spin textures having an opposite topological charge to that of the skyrmions. Therefore, chromium telluride can be a new paradigm of the skyrmion material family with promising prospects for future device applications. Magnetic skyrmions and large topological Hall effect are demonstrated in chromium telluride. The Curie temperature and magnetic anisotropy in Cr1+xTe2 can be controlled by the self‐intercalate concentration x. In Cr1.53Te2, which has a Curie temperature of 295 K and a relatively weak perpendicular magnetic anisotropy, room‐temperature skyrmions and topological Hall resistivity as large as ≈106 nΩ cm are observed.